Case Report: Extremely Early Detection of Preclinical Magnetic Resonance Imaging Abnormality in Creutzfeldt–Jakob Disease With the V180I Mutation - Koizumi, Ryuichi; Ueda, Naohisa; Mugita, Atsushi; Kimura, Katsuo; Kishida, Hitaru; Tanaka, Fumiaki (Frontiers in Neurology, 2021)
The diagnosis of presymptomatic Creutzfeldt–Jakob disease (CJD) is challenging. The levels of total tau protein, 14-3-3 protein, and protease-resistant isoform of prion protein (PrPres) in the cerebrospinal fluid; periodic sharp wave complexes on electroencephalography; and diffusion-weighted imaging (DWI) of brain magnetic resonance imaging (MRI) have all been used to diagnose symptomatic CJD, but none of these markers have been established in the diagnosis of presymptomatic CJD. Here, we report a case of genetic CJD with the V180I mutation in which a small punctate cortical hyperintensity was detected on DWI 6 months before symptom onset and 9 months before diagnosis. Presymptomatic CJD is currently impossible to diagnose because of the lack of established early diagnostic markers. However, since MRI is increasingly used in daily clinical practice, the chance detection of such DWI abnormalities would have important implications in terms of providing a clue to examine a highly specific early diagnostic marker to be developed in the future for CJD. This will allow presymptomatic intervention by disease-modifying therapy in the near future.